Analysis of potential changes in the Black Sea wave power for the 21st century - Aydogan, Burak; Gormus, Tahsin; Ayat, Berna; Carpar, Tunay (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This study aims to project wave power variations in the Black Sea throughout the 21st century. A spectral wave modeling study is done using the open-source software SWAN. Wind fields were downscaled with a two-layered system where the first layer is a radial basis function, and the second layer is a generalized linear model. Two representative pathways and two different global circulations models were considered. Mean wave power in the basin fluctuates around 4 kW/m and associated maximum wave powers in the basin could even reach 20 kW/m, mostly accounted for the winter season and the Western part of the basin. Although both increasing and decreasing wave power areas exist in the basin for different models and representative concentration pathways scenarios, future projections showed no distinguishable change in the spatial distribution of the wave power. At the end of the century, basin-averaged differences for the historical period are ranging between +0.14 kW/m and -0.32 kW/m. Seasonal variability is shown to be high. Spring has the biggest change in the basin-averaged wave power with a decrease of up to 20% considering all models and scenarios. Inter-annual variability is greater for the Climate Model Version 3 model. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Black sea; Wave energy; Climate change; Representative concentration pathways; Science & Technology - Other Topics; Energy & Fuels